(3fKQ GdLeGf aj JQGLe GdGYjGfs - (3CMeO Hf eMeO Hf Ydj Gdajhej GdMehj, CHh GdYHGS,J (B770 (3g` s
(3ChdgG (B:s
(3ajgG ef CKfGA SfI (B701 (3g` s
(3BNQgG (B:s
(3Edi SfI (B754 (3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B224 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B132s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B20 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B272 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs